Analyzing and Understanding Social Marketing Activities of Turkish Banking Corporations: Comparisons and Association Rule Learning - Pekdemir, Recep; Süer, Ayça Zeynep; Ercan, Melis; Önder, Emrah (Journal of Accounting and Finance, 2023)
This study addresses the question, “What is the extent of disclosures related to marketing social change as changing behavior to promote social good and well-being, any evidence from the Turkish banking industry?” To address this question, the study analyzes the social marketing activities of 12 banking corporations listed on the Borsa Istanbul in Turkey. For this, annual reports, sustainability reports, or integrated reports of those are examined from 2017 to 2021. It is aimed to compare the social marketing activities of banks in Turkey and trends that have been observed for years and banks. It is also aimed at determining the most frequent social marketing activities. The banks are involved mostly in the themes of environmental behaviors and community involvement behaviors. To observe the relationships between social marketing activities, “Association Rule Analysis with Apriori Algorithm” is applied. The management of the banks can use the findings of Apriori Algorithm in the strategic decision-making process if they are aware of the social marketing activities that rival banks are emphasizing and the relationships between these activities.